Indoor Navigation System Using Visual Positioning System with Augmented Reality - Yadav R.; Chugh H.; Jain V.; Baneriee P. (My University, 2025)
Although GPS is widely used for navigation purpose, but GPS uses satellite links for pinpointing the location. GPS is not suitable for using indoor navigation because satellite signals cannot penetrate tall buildings. Thus, we need an all-round solution which can help us navigate in an indoor environment of a large building such as, interior architecture of a shopping mall, etc. There are various indoor navigation systems, almost each one of them require external hardware infrastructure. In this paper, we proposed an augmented reality based indoor navigation system which can help us to navigate within large buildings using cameras mounted on our smartphones. © 2018 IEEE.